Meta AI y el aprendizaje de los estudiantes del bachillerato técnico en informática de la Unidad Educativa Babahoyo, periodo académico Octubre 2024 – Marzo 2025. - Cabrera Salavarria, María Isabel (2025)
In this curricular project research, the general objective is to evaluate the use of Meta AI in the learning of the students of the Technical Baccalaureate in computer science of the Educational Unit of Babahoyo during the academic period October 2024 March 2025. This study seeks to determine how Meta AI contributes to the development of meaningful learning and critical analysis skills. The methodology used for this study is of a mixed nature where qualitative and quantitative data obtained through direct observation, survey and literature review techniques were collected and analyzed. The object of study for data collection is a population that includes 311 students enrolled in the Technical High School of Computer Science at the Babahoyo Educational Unit and the sample of this is 173 students who were surveyed. In which an observation form and a questionnaire constructed by 10 closed questions with Likert scale were applied, applying these techniques to comply with the evaluation of the use of Meta IA. The scope of the research is descriptive using a non-experimental design in order to observe the study phenomenon in its natural context without manipulating the variables. The data obtained were analyzed using techniques such as documentary analysis to support the discussion of results between survey and observation, obtaining conclusions and recommendations, where it was evidenced that the use of Meta AI contributes to the significant learning of students, implementing the application in academic activities and leading students to use it frequently to solve their doubts in a quick way.